2010
DOI: 10.1007/s11104-009-0279-4
|View full text |Cite
|
Sign up to set email alerts
|

Organic and inorganic fertilizer effects on a degraded Patagonian rangeland

Abstract: The forest-steppe ecotone in NW Patagonia is a semiarid ecosystem affected by natural and anthropogenic fires, and overgrazing by sheep. Following a wild fire in the driest portion of this ecotone, a 3-year study was conducted to assess the impacts of a single application of inorganic and organic fertilizers on soil and vegetation recovery. Organic fertilizers were composts derived from biosolids and municipal solid wastes. Six treatments were evaluated: screened and unscreened biosolids compost and municipal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 39 publications
3
29
0
1
Order By: Relevance
“…The increase in soil C was likely derived from a combination of compost incorporation into soil and additions of newly fixed C from NPP. In a three-year study monitoring the effects of a one-time application of either inorganic or organic fertilizers in a degraded semiarid rangeland in Patagonia, Kowaljow et al (2010) observed a similar pattern of increase in soil organic C and enhanced microbial activity. Soil organic C formation and stabilization is promoted by management practices or technologies that increase the quantity of C inputs (Gentile et al 2011).…”
Section: Patterns In Soil Respiration and Greenhouse Gas Emissionsmentioning
confidence: 76%
See 1 more Smart Citation
“…The increase in soil C was likely derived from a combination of compost incorporation into soil and additions of newly fixed C from NPP. In a three-year study monitoring the effects of a one-time application of either inorganic or organic fertilizers in a degraded semiarid rangeland in Patagonia, Kowaljow et al (2010) observed a similar pattern of increase in soil organic C and enhanced microbial activity. Soil organic C formation and stabilization is promoted by management practices or technologies that increase the quantity of C inputs (Gentile et al 2011).…”
Section: Patterns In Soil Respiration and Greenhouse Gas Emissionsmentioning
confidence: 76%
“…These effects may last several years. The longlasting effects of a single application of compost could serve to buffer impacts of decreasing precipitation predicted for some regions with climate change (Stavast et al 2005, Kowaljow et al 2010.…”
Section: Patterns In Soil Respiration and Greenhouse Gas Emissionsmentioning
confidence: 99%
“…Goat manure undergoes fermentation and heats up more quickly than cow manure or pig manure. (Kowaljow, Mazzarino, Satti, & Jiménez-Rodríguez (2010) suggested that organic fertilizers could enhance soil organic C, total N, extractable P and mineralization of N. Organic amendments are able to provide a balance and regular plant nutrition through gradual decomposition by microorganisms, slower mineralization and slower release. Farm yard manure can improve the property of soil physics, good for root development and plant growth, in order to obtain yields with higher quality (Chatterjee & Paul, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…A long-term experiment was established in a degraded, burned site of NW Patagonia in 2004, applying a single moderate dose of urban composts and an inorganic fertilizer; the most important effects 3 years after application were increases of soil organic C, total N, and microbial activity (Kowaljow et al 2010). Composts also led to increased aboveground plant biomass but this effect was higher with inorganic N-P fertilization.…”
Section: Introductionmentioning
confidence: 99%